A semi-resolved CFD-DEM model for seepage-induced fine particle migration in gap-graded soils. (August 2018) - Cheng, Kuang; Wang, Yin; Yang, Qing
Abstract: A semi-resolved CFD-DEM model is proposed to model the seepage-induced fine particle migration within the gap-graded soils consisting of fine and coarse particles. In this model, a resolved method, i.e., Fictitious Domain (FD) method is used to resolve the fluid flow around the coarse particles and the un-resolved approach based on the locally averaging theory is adopted to describe the interactions between the fine particles and the fluid flow for the computational efficiency. The semi-resolved CFD-DEM model is validated using several simple examples and is further used to analyze the fine particle migration and associated piping erosion in gap-graded soils.